please slove it argent
Attachments:
![](https://hi-static.z-dn.net/files/d54/5185082aac8184c0ccef2fd6181bf041.jpg)
Answers
Answered by
1
it is the best solution
you hope
follow
Attachments:
![](https://hi-static.z-dn.net/files/d94/0b2924466c15c4e33c88050eb9e2376a.jpg)
chitrasaindane:
thanks
Answered by
1
Answer:
Step-by-step explanation:
LHS = cos^2 A + tan^2 A - sin^2 A - cos^2 A / sin^2 A
= tan^2 A - sin^2 A / sin^2 A
= 1/cos^2 A - 1
= sec^2 A - 1
= tan^2 A = RHS
LHS = RHS
Hence, proved.
Similar questions